Developmental trajectory of the late positive potential: Using temporal‐spatial PCA to characterize within‐subject developmental changes in emotional processing - Mulligan, Elizabeth M.; Infantolino, Zachary P.; Klein, Daniel N.; Hajcak, Greg (Psychophysiology, 2020)
The late positive potential (LPP) is characterized by temporal and spatial changes across development—though existing work has primarily relied on visual or statistical comparisons of relatively few electrodes and averaged activity over time. The current study used an empirically based approach to characterize temporal and spatial changes in ERPs over time. Data were utilized from a large longitudinal study (N = 380) in which the LPP was recorded to pleasant, neutral, and unpleasant pictures around age 9 and again around age 12. Age 9 ERPs were subtracted from age 12 ERPs for all three image types; the resulting ERPs for each subject at each electrode site were then submitted to a temporospatial principal component analysis (PCA). A PCA factor was greater in amplitude for emotional pictures compared to neutral pictures between ages 9 and 12, evident as an occipital negativity and frontocentral positivity that peaked approximately 850 ms following picture presentation. Furthermore, the factor scores to emotional pictures for this component increased as a function of age 12 pubertal development, consistent with the notion that the LPP shifts from occipital to more frontocentral sites in relation to developmental changes from childhood to adolescence. A similar factor was observed when PCA was applied to all ERPs from both ages 9 and 12. Using temporospatial PCA on ERPs collected from the same subjects over time—especially within‐subject subtraction‐based ERPs—provides a concise way of characterizing and quantifying within‐subject developmental changes in both the timing and scalp distribution of ERPs. This work presents an empirically based approach to characterizing developmental changes in ERPs by performing temporospatial PCA on ERPs from two within‐subject assessments. This method provides a holistic metric representing a linear combination of all time points and electrode sites and may be more sensitive to developmental changes in ERPs. Finally, the present study extends previous developmental studies of the LPP by demonstrating that developmental shifts in the LPP to emotional images are correlated with pubertal development, suggesting that these changes in emotional processing occur as a function of typical development in adolescence.